2016
DOI: 10.1186/s13068-016-0548-4
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the microbial ecology resulting from different inoculation strategies for biogas production from waste products of the bioethanol/sugar industry

Abstract: BackgroundDuring strategic planning of a biogas plant, the local availability of resources for start-up and operation should be taken into consideration for a cost-efficient process. Because most bioethanol/sugar industries in Brazil are located in remote areas, the use of fresh cattle manure from local farms could be a solution for the inoculation of the biogas process. This study investigated the diversity and dynamics of bacterial and archaeal communities and the performance of biogas reactors inoculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…As archaeal communities in rumen and manure environments are generally dominated by methanogens (39) and many of them can establish in both environments (12), storage of dairy slurry might not result in significant shifts in the diversity of archaea or methanogens (40). Indeed, an earlier study (41) identified similar methanogenic archaeal communities from fresh diary manure and a mixed inoculum obtained from different biogas reactors, although with a higher abundance in the latter, which is consistent with the current study. The relatively higher diversity of bacteria in RS than in fresh manure was not expected, but the source of RS might have influenced the diversity.…”
Section: Discussionsupporting
confidence: 91%
“…As archaeal communities in rumen and manure environments are generally dominated by methanogens (39) and many of them can establish in both environments (12), storage of dairy slurry might not result in significant shifts in the diversity of archaea or methanogens (40). Indeed, an earlier study (41) identified similar methanogenic archaeal communities from fresh diary manure and a mixed inoculum obtained from different biogas reactors, although with a higher abundance in the latter, which is consistent with the current study. The relatively higher diversity of bacteria in RS than in fresh manure was not expected, but the source of RS might have influenced the diversity.…”
Section: Discussionsupporting
confidence: 91%
“…in a plot showing also the δ 13 C CH4 and δ 2 H CH4 values. The combination of carbon and hydrogen isotope data sometimes allows a more detailed characterization of the potential dominant methanogenic pathways during biogas reactor experiments , . The δ 2 H CH4 values in the batch experiment ranged between −271 and −319 ‰ and clearly differed from the values of the maize silage mono‐digesting CSTR data scattered in a narrow range between −267 and −280 ‰.…”
Section: Resultsmentioning
confidence: 99%
“…In countries with few AD plants separated by long distances such as Brazil, arranging proper inocula is difficult. This was successfully addressed by the evaluation of reactor inoculation with fresh cattle manure as a locally available, alternative inoculum (Janke et al, 2016c;Leite et al, 2016). Animal manure is rich in microorganisms from animal digesting system, as well important macronutrients and trace elements (Feng et al, 2020).…”
Section: Biogas Production and Utilization Anaerobic Digestionmentioning
confidence: 99%